INTERNALISASI NILAI PAI TRANSFORMATIF DALAM MEMBENTUK KARAKTER, MORALITAS, DAN PERILAKU SOSIAL PESERTA DIDIK - Muh. Zakki Amrulloh; M. Nurul Humaidi; Budi Sunariyanto; Jefri Mardiansyah A.; Muhammad Rondi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the internalization of transformative Islamic Religious Education values in shaping students’ character, morality, and social behavior. This research used a qualitative approach with a literature review method. The data were obtained from literature discussing transformative Islamic Religious Education, transformative learning, value internalization, character education, morality, the role of Islamic Religious Education teachers, and students’ social behavior. The data were analyzed through thematic content analysis, including data reduction, categorization, interpretation, and synthesis. The findings show that the internalization of transformative Islamic Religious Education values takes place through value transformation, value transaction, and value transinternalization. This process is strengthened through critical reflection, teacher role modeling, religious habituation, active learning, and a supportive school culture. The main findings indicate that transformative Islamic Religious Education contributes to the development of religious character, honesty, discipline, responsibility, tolerance, care, and cooperation. This study concludes that transformative Islamic Religious Education does not only support students’ mastery of religious knowledge but also shapes their moral awareness and positive social behavior.